2006
DOI: 10.1002/jsc.772
|View full text |Cite
|
Sign up to set email alerts
|

Strategic choices and change in non-profit organizations

Abstract: ᭹More than ever, non-profit organizations are embracing strategy in order to navigate the rapid change in their operating environment. This study draws on the Miles and Snow generic strategies (prospector, analyser, defender and reactor) to examine: (a) current and previous strategic choices of non-profit organizations and (b) the role of government funding in the change (if any) from one strategic type to another. ᭹The study finds that while there were movements from and towards the four strategic types, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 26 publications
1
37
0
6
Order By: Relevance
“…Nonprofits are particularly sensitive to the social context because of resource and socio-political factors. Stakeholder relationships are instrumental to managing these nonfinancial systems (Akingbola 2006). Managing and developing relationships create social capital (King 2004;Putnam 2000).…”
Section: Social Capitalmentioning
confidence: 99%
“…Nonprofits are particularly sensitive to the social context because of resource and socio-political factors. Stakeholder relationships are instrumental to managing these nonfinancial systems (Akingbola 2006). Managing and developing relationships create social capital (King 2004;Putnam 2000).…”
Section: Social Capitalmentioning
confidence: 99%
“…Indeed they have gradually provided a useful cookbook for many NGOs from which to choose and implement any of the proper techniques to suit their own purposes and to help in achieving their goals. It can be concluded that more than ever NGOs are embracing strategy in order to rapidly change within their operating environment (Akingbola, 2006). Wright et al (1994) emphasize that strategic management plays a vital role in enhancing organizational effectiveness in all types of organizations, large or small, international or domestic, diversified or single product, and profit or non-profit.…”
Section: Strategic Management and Ngos: A Brief Overviewmentioning
confidence: 99%
“…Gil-Estallo et al (2006) assert that NGOs have a mission, strategy, and goals different from those organizations looking for profits. While Akingbola (2006) emphasizes that more than ever NGOs are embracing strategy in response to the rapid change in their operating environment.…”
Section: Strategic Awareness Of the Managersmentioning
confidence: 99%
“…Even successful changes may not be short-lived when competitors are able to mimic the shift (Wernerfelt & Karnani, 1987). Further, a potentially successful strategic change must endure efforts to return to the former strategy when those whose careers may suffer because of the change resist executing the strategy (Akingbola, 2006;Gaertner, 1989). Strategic change can challenge the assumptions of all organizational members and may be difficult to implement even with employee support (Boyett & Currie, 2004).…”
Section: Commitment Flexibility and Dynamic Strategiesmentioning
confidence: 99%